Changes of myofibrilliar protein and texture in black tiger shrimp (Penaeus monodon) during ice storage - Abdul Al-Hafiz Ismail (Institut Akuakultur Tropika, 2011)
Research to address the concern for post-harvest quality losses in fisheries have not been done in-depth especially for our local seafood products. These losses will occur due to increasing ambient temperature and stagnation of transfer after being harvest. Quality deterioration will affect the consumer or market acceptences thus decrease the demand on the product. In this study, black tiger shrimp {Penaeus monodon) was obtained from a local supplier in Marang, Terengganu, killed and stored in an insulated box at 0°C for 9 days. For every storage period, the shrimp was processed prior to SDS-PAGE analysis and texture analysis.